2016
DOI: 10.1038/nbt.3663
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure regulation by CD4+ lymphocytes expressing choline acetyltransferase

Abstract: Blood pressure regulation is known to be maintained by a neuro-endocrine circuit, but whether immune cells contribute to blood pressure homeostasis has not been defined. We previously described that CD4+ T lymphocytes that express choline acetyltransferase (ChAT), which catalyzes the synthesis of the vasorelaxant acetylcholine, relay neural signals1. Here we show that these CD4+ CD44high CD62Llow T helper cells by gene expression are a distinct T cell population defined by ChAT (CD4 TChAT). Mice lacking ChAT e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
82
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(84 citation statements)
references
References 38 publications
2
82
0
Order By: Relevance
“…T cells have been shown to play a role in atherosclerosis, and chronic vascular inflammation, mediating chronic hypertension. These current findings (Olofsson et al, 2016) suggest that a dysregulation of ChAT + CD4 + T cells could also contribute to the development of hypertensive phenotype. Acetylcholine producing CD4 + T cells in spleen, and possibly other tissues, are regulated by neural signals traveling in the vagus and splenic nerves (Rosas-Ballina et al, 2011), which provides a regulatory mechanism that can be therapeutically explored.…”
Section: Reflexes In Neuro-immune Communicationsupporting
confidence: 55%
See 2 more Smart Citations
“…T cells have been shown to play a role in atherosclerosis, and chronic vascular inflammation, mediating chronic hypertension. These current findings (Olofsson et al, 2016) suggest that a dysregulation of ChAT + CD4 + T cells could also contribute to the development of hypertensive phenotype. Acetylcholine producing CD4 + T cells in spleen, and possibly other tissues, are regulated by neural signals traveling in the vagus and splenic nerves (Rosas-Ballina et al, 2011), which provides a regulatory mechanism that can be therapeutically explored.…”
Section: Reflexes In Neuro-immune Communicationsupporting
confidence: 55%
“…The discovery of the inflammatory reflex generated a great deal of interest in studying the vagus nerve-splenic nerve axis in the regulation of immune function in a variety of conditions, including antibody secretion following exposure of B cells to blood-borne antigen and modulating cell trafficking and splenic lymphoid architecture (Mina-Osorio et al, 2012), IBD (Ji et al, 2013; Munyaka et al, 2014), renal ischemia-reperfusion injury (Inoue et al, 2016), and T cell activation and egression from the spleen in experimental hypertension (Carnevale et al, 2016). In addition, research initially performed to further characterize T-ChAT cells led to the important discovery that a specific subset of these cells mediate blood pressure regulation (Olofsson et al, 2016). Although it is known that acetylcholine causes vasodilation resulting in decreased blood pressure, blood vessel innervations are almost exclusively catecholaminergic and the origin of acetylcholine associated causing endothelium-derived relaxation has remained enigmatic for a long time.…”
Section: Reflexes In Neuro-immune Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Although increasing evidence indicates the importance of parasympathetic nerves in the immune function of patients with other systematic diseases, studies of neuroimmune regulation in the field of AR have rarely been reported. 11,16,[21][22][23] In the present study, by establishing an in-vitro neuroimmune coculture model of D-U87 neurons and CD4 + T cells, we observed that cholinergic neuron-like D-U87 cells promoted the polarization of CD4 + T cells from patients with AR toward Th2 cells, and inhibition of the cholinergic activity of D-U87 cells by IB decreased the preferential Th2 polarization by modulating Akt signaling. To facilitate investigation of the role of cholinergic nerve function in patients with AR, an in-vitro cholinergic neuron model must be established.…”
Section: Discussionsupporting
confidence: 54%
“…Activation of endothelial cholinergic receptors promotes release of nitric oxide that reduces blood pressure by relaxing vascular smooth muscle cells . CD4 T ChAT are found in murine blood, and mice deficient in CD4 T ChAT show significantly increased blood pressure and their cardiovascular physiology is consistent with an increased systemic vascular resistance . These observations indicate that CD4 T ChAT regulates blood pressure by providing a cholinergic signal to vascular endothelial cells, and it is conceivable that neurotransmitter‐releasing immune cells may interact with nerves and organs to regulate physiology in additional ways not yet discovered.…”
Section: Anti‐inflammatory Mechanisms Of Vagus Nerve Stimulationmentioning
confidence: 99%